Plant grow harvest repeat : grow a bounty of vegetables, fruits, and flowers by mastering the art of succession planting - Cowden, Meg McAndrews (Timber Press, 2022)
"Chapter 1 will focus on succession in the landscape, including lessons from prairies and woodlands. Chapter 2 moves on to how succession can work in the garden. Chapter 3 is about how to "layer" succession onto the home landscape, and the final chapter talks about the foundations of successful succession planting. This approach to gardening has not been explored in such depth and detail in other books; the link between natural processes and the garden should appeal to a wide spectrum of gardeners"--